How vision works the physiological mechanisms behind what we see - Daw, Nigel (New York : Oxford University Press, 2012)
This text covers all aspects of the visual system from sensory aspects to eye movements, attention, and visual memory in a brief format. Each chapter describes the psychology, followed by where in the brain that aspect is dealt with, the properties of the cells in that area, and what happens if a patient has a lesion or stroke in that area.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Vision; Visual perception